2020
DOI: 10.5829/ije.2020.33.02b.15
|View full text |Cite
|
Sign up to set email alerts
|

Radar Absorption Performance of Fe3O4/AC/PANI Nanocomposites Prepared from Natural Iron Sand

Abstract: In this work, the Fe3O4 nanoparticles from natural iron sand were combined with active carbon (AC) and polyaniline (PANI) to obtain Fe3O4/AC/PANI nanocomposites with mass variations of the AC of 0.1, 0.2, 0.3, 0.4, and 0.5 g. The crystalline phase of Fe3O4/AC/PANI nanocomposites formed from Fe3O4 with PANI having an amorphous phase. Meanwhile, the crystalline phase of AC was unmatched because of its very small composition. The presence of AC was observed through vibrations from the CC and COOH functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…According to equation (18), it can be seen that the eddy current loss depends on the particle diameter (d) and electrical conductivity (σ). μ0 is the magnetic permeability constant in a vacuum [42].…”
Section: Microwave Absorption Properties Of the Prepared Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to equation (18), it can be seen that the eddy current loss depends on the particle diameter (d) and electrical conductivity (σ). μ0 is the magnetic permeability constant in a vacuum [42].…”
Section: Microwave Absorption Properties Of the Prepared Materialsmentioning
confidence: 99%
“…Also, the optical properties of Fe3O4/AC/PANI nanocomposites have been shown by increasing the energy gap and decreasing the absorption wavelength. Interestingly, the improving in the weight ratio of carbon causes the adsorption of Fe3O4/AC/PANI nanocomposites [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology played an important role in various applications, especially the huge systems like nuclear reactors in their cooling [75,76]. Recently modern military radars applied nanotechnology in the cooling system of the radar, and found that the efficiency of the waste heat recovery heat exchanger increased for nanofluids, that huge among of heat can be calcified as pollution, therefore, many researchers and environmental activists trying to reduce and minimize thermal pollution and recover the energy waste [77][78][79].…”
Section: Applications Of Nanofluidsmentioning
confidence: 99%